Role of Art Therapy Methods in Future Social Workers’ Professional Activity - Liubov Poltorak (Pedagogical Discourse, 2014)
The article reviews topicality of art therapy methods in social work, determines main problems and groups of customers where art therapy is mainly used. Author declares that today social workers use methods of art therapy mostly with such categories of their customers as: families, people with physical disabilities, gifted children, children with mental disabilities, teens, addicts and their families, HIV-infected persons. Main activities where art therapy is appropriately used where systematized and separated based on the analysis of scientific literature. They are: psychological, educational, preventive, educational and entertaining. Use of each art therapy method is reviewed according to separate examples.Analyzes that were held show that art therapy methods are important and are necessary working with different groups of clients. Use of art therapy methods allows social workers to consider personality traits, life conditions and provide most effective process of influence on personality.